External anatomical shapes reconstruction from turntable image sequences using a single off-the-shelf camera - Teresa Cristina de Sousa Azevedo (2007)
Three-dimensional (3D) human body reconstruction and modeling from multiple two-dimensional (2D) images is a topic of great interest and research but still remains a difficult problem. Volu-metric based methods are commonly used to solve this type of problem. With those methods, from a turntable image sequence of an object, a 3D model can be built. The final goal of the work presented in this paper is to reconstruct all-round 3D models of the human body, using a single off-the-shelf camera and volumetric tech-niques, with the best accuracy and photorealistic appearance.